1990
DOI: 10.1093/eurheartj/11.suppl_e.20
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular lipid deposition in atherosclerosis

Abstract: Atherosclerotic lipid deposits found in the core region of fibrous plaques are almost entirely extracellular, but it is not known whether they are derived from necrosis of cells containing accumulated lipid or from direct extracellular lipid accumulation. New evidence pertaining to this question has been obtained through the use of recently developed techniques for preserving and staining lipids in electron microscopy, and through a detailed morphologic and chemical examination of human aortic fibrolipid lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…In summary, we have now demonstrated that many of the toxic events that are thought to occur within the atherosclerotic lesion, such as FC accumulation, 32 increased phospholipid synthesis, 38,50 -52 FC crystallization, 38,53,54 and apoptosis and necrosis, 39,55 can be reproduced in a model foam cell culture system. It is evident that in FC content in a foam cell can disturb the homeostatic balance and provoke toxic responses, such as necrosis and apoptosis.…”
Section: Cholesterol Crystal Formationmentioning
confidence: 77%
“…In summary, we have now demonstrated that many of the toxic events that are thought to occur within the atherosclerotic lesion, such as FC accumulation, 32 increased phospholipid synthesis, 38,50 -52 FC crystallization, 38,53,54 and apoptosis and necrosis, 39,55 can be reproduced in a model foam cell culture system. It is evident that in FC content in a foam cell can disturb the homeostatic balance and provoke toxic responses, such as necrosis and apoptosis.…”
Section: Cholesterol Crystal Formationmentioning
confidence: 77%
“…particle fusion, we next used a fusion assay based on 1 H NMR spectroscopy (49). In this assay, fusion of lipoprotein particles is detected by size-dependent chemical shifts in the 1 H NMR resonances of lipoprotein lipids. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…extensively, as shown by the abundant generation of trichloroacetic acid-soluble apoB-100 fragments. The extensive degradation of apoB-100 in LDL by cathepsin F was accompanied by formation of aggregated and fused particles, as demonstrated by the increased turbidity of the samples, by the increased flotation of the particles in ultracentrifugation, by 1 H NMR spectrometry, and by electron microscopy. Interestingly, electron microscopy revealed that the proteolyzed particles resembled the lipid droplets found in the atherosclerotic human arterial intima (56 -58).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations